Needful things [videorecording (Blu-Ray)] - Richter, W. D.; Sydow, Max von, 1929-2020; Harris, Ed, 1950-; Bedelia, Bonnie, 1946-; King, Stephen, 1947- (KL studio classics., 2023)
Terror grips a small New England town in this Stephen King thriller.